Secado de extractos de cafe concentrados con tratamiento enzimatico - Ruiz R, D.=700 1 Riaño L, C.E.; Orozco G, L.
(Es, En)
Ilus., 15 ref.
Keywords: COFFEA ARABICA; CAFE INSTANTANEO; SECADO; ENZIMAS; LIOFILIZACION; INDUSTRIALIZACION; COLOMBIA